Prevalence of allergic rhinitis, and symptoms as indicators of risk in schoolchildren of the Puebla Northern Mountain Range - Eleazar Mancilla-Hernández; Evaristo González-Solórzano (Revista Alergia México, 2018)
Background: According to the ISAAC study, the prevalence of allergy disease is reported to have increased.